ZAKAT DALAM SISTEM EKONOMI ISLAM: MENSEJAHTERAKAN UKM DI INDONESIA - Izzun Khoirun Nissa; Mochammad Taufik Nur Sapto Wardoyo (JASIE, 2023)
Poverty is a multidimensional problem that is not only related to zakat and Islamic economics but also related to other fields. One of the instruments that can be used to overcome the problem of poverty and empower people is zakat. Zakat is a number of assets that must be issued because it has reached certain conditions. This research is a descriptive research that aims to describe and find out Zakat in the Islamic Economic System: Prospering SMEs (small and medium enterprises) in Indonesia through existing data and analysis. From the research results it is expected to know that the importance of the role of zakat and the Islamic economic system in improving the welfare of SMEs (small and medium enterprises) and becoming an effort to increase the Islamic economy as well as minimizing poverty and prospering SMEs (small and medium enterprises) in the current era of globalization.